Residuum oralne w średniopolskich utworach dedykacyjnych - Tutak, Kinga (Slavia Occidentalis, 2015)
The act of dedications played a fundamental role in oral societies. It was of equal importance to chirographic and typographic communities as an element of a work’s para-textual frame. In selected Polish dedication works from the 16th and the 17th centuries, the author of the article looks for an oral residuum which could be identified in the complex structure of this type of expression, rooted in rich tradition and shaped in the time of oral literature. In particular, the author of the article proves that even a characteristic feature of the written sub-code like punctuation was subordinated to the listening audience.